Writing as Witnessing, Poetry as Agency of Aid: The Five Poems from Typhoon Yolanda Relief Anthologies - Vac Ann C. Dadia (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
The strong typhoon Yolanda (international name: Haiyan), which buffeted the central Philippine region on November 2013 spurred the publication of several relief anthologies, so-called because they were primarily intended to raise funds for the disaster victims. This paper argues that as a distinct method of volunteerism, the poems that comprise the Yolanda relief anthologies are ecopoems which not only bear intrinsic ecological themes that confront an environment in crisis but also embody what Filipino poet Luisa A. Igloria describes as a